THE METHOD OF GREAT MOTHERS RAISING GREAT GENIUSES (Academia Science Repository, 2023)
This article talks about the most beautiful ways to approach child education, which is the greatest and first task of mankind. Through the article, it can become the most beautiful example school for raising geniuses by eliminating the defects that arise in child education in our time.